Transitional Care Management in Persons With Dementia After Heart Failure Hospitalization and Skilled Nursing Facility Care - Bayer, Thomas A.; Varma, Hiren; Hollmann, Peter A.; Gozalo, Pedro L. (Journal of the American Geriatrics Society (JAGS), 2025)
ABSTRACT Background Dementia complicates care transitions, such as discharge from heart failure hospitalization to a skilled nursing facility (SNF) and then to home. Transitional care management (TCM), a bundled service that includes telephone communication within 2 business days and an office visit within 14 days, potentially addresses this problem. Methods We analyzed trends in TCM among Medicare beneficiaries with dementia hospitalized for heart failure in 2013–2017, comparing hospital–home discharges to hospital–SNF–home discharges. We then used a retrospective cohort study to estimate the risk‐adjusted association of TCM with successful discharge home. Results TCM occurred in 45 (2.3%) of 1990 eligible hospital–SNF–home discharges in year 2013, increasing to 205 (9.8%) of 2095 eligible in year 2017. In a cohort of 11,376 hospital–SNF‐home transitions, the relative risk (95% CI) of successful community discharge was 1.24 (1.11–1.40) with TCM compared with no office visit within 14 days of discharge or TCM. Conclusions Persons with dementia transitioning from heart failure hospitalization to SNF to home receive TCM less frequently than persons discharged directly home from the hospital. Nonetheless, TCM is associated with successful discharge in this vulnerable group of patients.